2012
DOI: 10.3390/ijerph9030722
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Social Factors and Suicidal Behavior in Older Adulthood

Abstract: Suicide in later life is a global public health problem. The aim of this review was to conduct a systematic analysis of studies with comparison groups that examined the associations between social factors and suicidal behavior (including ideation, non-fatal suicidal behavior, or deaths) among individuals aged 65 and older. Our search identified only 16 articles (across 14 independent samples) that met inclusion criteria. The limited number of studies points to the need for further research. Included studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
178
0
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(206 citation statements)
references
References 95 publications
9
178
0
19
Order By: Relevance
“…Entre los trastornos mentales predominantes en las personas que se suicidan destacan los trastornos afectivos y la esquizofrenia 16,[17][18][19] . Así también otras investigaciones dan cuenta de que problemas financieros, dificultades en las relaciones sociales, conflictos familiares, aislamiento social y soledad; son la razones más frecuentes de suicidio 20,21 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Entre los trastornos mentales predominantes en las personas que se suicidan destacan los trastornos afectivos y la esquizofrenia 16,[17][18][19] . Así también otras investigaciones dan cuenta de que problemas financieros, dificultades en las relaciones sociales, conflictos familiares, aislamiento social y soledad; son la razones más frecuentes de suicidio 20,21 .…”
Section: Discussionunclassified
“…Ya que tal cual como se refleja anteriormente existe evidencia respecto de potenciales factores de riesgo asociados a la mortalidad por suicidio, los que en su gran mayoría están relacionados a población europea y norteamericana [16][17][18][19][20][21] ; sin embargo, existe poca información disponible a nivel latinoamericano.…”
Section: Discussionunclassified
“…22 The authors reported some evidence of the association of all of these factors with suicidal behaviour, although the studies were inconsistent. The authors conceptualized the different factors as components of social connectedness and concluded that limited social connectedness was associated with suicidal thoughts and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO's World Suicide Report, the global agestandardised suicide rate for 2012 was 11.4 per 100,000 population, which translates into 804,000 suicide deaths annually worldwide (WHO, 2014). A significant body of work has focused on describing high-risk populations, such as clinical populations with mental illness and general populations whose members experience social stressors and adverse life events (Cavanagh et al, 1999;Fässberg et al, 2012;Foster, 2011;Gonda et al, 2012;Stack, 2014). A range of sociodemographic, psychological and clinical risk factors have also been identified (Hawton et al, 2003b;Mościcki, 1997;O'Connor, 2011;O'Connor and Nock, 2014;WHO, 2014).…”
Section: Introductionmentioning
confidence: 99%